2001
DOI: 10.1111/j.1744-7429.2001.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Mortality in Hawaiian Rain Forest: The Role of Small‐Scale Physical Disturbance1

Abstract: Most montane rain forests on the island of Hawaii consist of a closed canopy formed by Cibotium spp. tree ferns beneath an open canopy of emergent Metrosideros polymorpha trees. We used artificial seedlings to assess the extent to which physical disturbance caused by the senescing fronds of tree ferns and the activities of feral pigs might limit tree regeneration. Artificial seedlings were established terrestrially (N= 300) or epiphytically (N = 300) on tree fern stems. Half of the seedlings on each substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Unlike the short sections of wood deposited in our debris treatments, fallen branches resulting from hurricane winds have fewer contact points with the ground and the vulnerable apical meristems of ferns. Ferns in the understory of wet tropical forests are naturally subject to branch and leaf fall throughout their lives (Drake and Pratt, 2001). Long-term studies in the LEF prior to and following Hurricane Georges have revealed infrequent terrestrial fern mortality: just three of 96 monitored individuals of T. deltoidea, and none of the 57 monitored individuals of C. borinquena died in the years after Hurricane Georges (Sharpe, unpublished data).…”
Section: Fern Mortalitymentioning
confidence: 99%
“…Unlike the short sections of wood deposited in our debris treatments, fallen branches resulting from hurricane winds have fewer contact points with the ground and the vulnerable apical meristems of ferns. Ferns in the understory of wet tropical forests are naturally subject to branch and leaf fall throughout their lives (Drake and Pratt, 2001). Long-term studies in the LEF prior to and following Hurricane Georges have revealed infrequent terrestrial fern mortality: just three of 96 monitored individuals of T. deltoidea, and none of the 57 monitored individuals of C. borinquena died in the years after Hurricane Georges (Sharpe, unpublished data).…”
Section: Fern Mortalitymentioning
confidence: 99%
“…For each seedling we recorded species, location, size, and rooting substrate (i.e., soil, root mat, rock, log, or tree fern). We included tree ferns as a rooting substrate because many trees establish epiphytically in Hawaiian forests (Drake and Pratt 2001). Each species was in a different genus, so hereafter we refer to species by their genus names (see Table 2 for complete names).…”
Section: Seed Rain and Seedling Demography Censusesmentioning
confidence: 99%
“…First, A. koa could provide revenue to the landowner without cattle grazing, an advantage because cattle grazing is highly destructive to native understory. Because the Hawaiian flora evolved in the absence of mammalian grazers, native understory plants have not evolved defenses against herbivory by cattle (Scowcroft, 1983;Scowcroft and Giffin 1983;Scowcroft and Conrad 1992;Blackmore andVitousek 2000, Drake andPratt 2001;Denslow et al 2006). Cattle consume tree seedlings and browse saplings, inhibiting forest regeneration and thinning the forest canopy over time (Scowcroft 1983;Stone 1985).…”
Section: Discussionmentioning
confidence: 98%